Echocardiographic systolic and diastolic function alterations in multiple myeloma patients treated with Carfilzomib. (8th February 2021) - Mingrone, G; Astarita, A; Maffei, I; Cesareo, M; Airale, L; Bruno, G; Vallelonga, F; Catarinella, C; Salvini, M; Bringhen, S; Gay, F; Veglio, F; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Carfilzomib improves the prognosis of multiple myeloma (MM) patients, but significantly increases cardiovascular toxicity. The timing and effect of carfilzomib therapy on left ventricular function is still under investigation. Purpose: We sought to assess the echocardiographic systo-diastolic changes, including global longitudinal strain (GLS), in patients treated with carfilzomib and to identify predictors of increased risk of cardiovascular adverse events (CVAEs) during therapy. Methods: 88 patients with MM performed a baseline cardiovascular evaluation comprehensive of transthoracic echocardiogram (TTE) before the start of Carfilzomib therapy and after about 6 months. All patients were clinically followed-up to early identify the occurrence of CVAEs for the whole therapy duration. Results: After Carfilzomib treatment, mean GLS slightly decreased (-22.2% ± 2.6 vs -21.3% ± 2.5; p < 0.001). 58% of patients experienced CVAEs during therapy: 71% of them had uncontrolled hypertension, 29% had major CVAEs or CV events not related to arterial hypertension. GLS variation during therapy was not related to an increased risk of CVAEs; however, patients with baseline GLS ≥ -21% and/or left ventricular ejection fraction (LVEF) ≤ 60% had an increased risk of major CVAEs (OR = 6.2, p = 0.004; OR = 3.7, p = 0.04, respectively). Carfilzomib led to an increased risk of diastolic dysfunction (5.6% vs 13.4% p = 0.04) and to a rise in E/e' (8.9 ± 2.7 vs 9.7 ± 3.7; p = 0.006). Conclusions: Carfilzomib leads to early LV function impairment early demonstrated by GLS changes and diastolic dysfunction. Baseline echocardiographic parameters, especially GLS and LVEF, might improve cardiovascular risk stratification before treatment.